NO Reactions Over Ir-Based Catalysts in the Presence of O2 - Mingxin Guo; Rongshu Zhu; Minhua Dong; Feng Ouyang (E-Journal of Chemistry)
The behaviour of a series of Ir-based catalysts supported on SiO2, ZSM-5 and γ-Al2O3 with various Ir loadings prepared by impregnation method was conducted by temperature programmed reaction (TPR) technique. The result implies that NO is oxidized to NO2 while simultaneously being reduced to N2 or N2O in the NO reactions over iridium catalysts. The surface active phase over iridium catalysts that promote the NO reactions is IrO2. The catalytic activity increases with the increase of the Ir loading and support materials have a little effect on the catalytic activity. When the loading is less than 0.1%, the catalytic activity was found to be dependent on the nature of support materials and in order: Ir/ZSM-5>Ir/γ-Al2O3>Ir/SiO2. When the loading is higher than 0.1%, the catalytic activity for NO oxidation is in order: Ir/ZSM-5>Ir/SiO2>Ir/γ -Al2O3, which is correlated with Ir dispersion on the surface of support materials and the catalytic activity for NO reduction is in sequence: Ir/γ -Al2O3>Ir/SiO2>Ir/ZSM-5, which is attributed to the adsorbed-dissociation of NO2. Compared to Pt/γ-Al2O3, Ir/γ-Al2O3 catalyst is more benefit for the NO reduction.